Simulation of fire resistance behaviour of pultruded GFRP beams – Part II: Stress analysis and failure criteria. (15th March 2018) - Morgado, T.; Silvestre, N.; Correia, J.R.
Abstract: This two-part paper presents a numerical study on the fire resistance behaviour of pultruded GFRP profiles with square tubular cross-section simultaneously subjected to four-point bending and the standard fire of ISO 834. The first part [1] presented the numerical models and results focused on the most relevant kinematic issues (deflections and strains), while this second part (present paper) reports numerical results associated to the static issues, particularly the evolution of stress distributions and failure initiation with fire exposure time. The paper first presents and discusses the evolution of stress distributions in both longitudinal and transversal directions of an unprotected GFRP beam under one-side fire exposure (reference beam). Next, the influence of using a fire protection system and exposing the beams to fire in three sides is assessed by comparison with the case of reference beam. Additionally, the Tsai-Hill failure (initiation) criterion was used to identify the zones (sections and points) of GFRP beams that are most sensitive to failure due to high temperatures. The numerical results obtained show that (i) longitudinal stresses across the section become highly nonlinear as a result of temperature increase; (ii) shear stress diagram is severely affected by fire exposure in three sides; (iii) transversal stresses are negligible compared to the longitudinal and shear ones; and (iv) the collapse of beams (considering Tsai-Hill failure analysis) occurs due to top flange and web (top part) failure, which generally agrees with experimental observations.